Phenanthro[9,10‑d]imidazoles: An Unexpected Synthetic Route - Springer, Bastian L.; Holzschneider, Kristina; Mohr, Fabian; Kirsch, Stefan F. (Synthesis, 2023)
A new synthetic route for the synthesis of phenanthro[9,10‑d]imidazoles is described. Through aminolysis of easily accessible 10,10-diazidophenanthren-9(10H)-one with nucleophilic amines, a self-condensation is triggered that results in the formation of the target phenanthro[9,10‑d]imidazoles. The molecular structures were studied by X-ray single crystallography, and the optical properties of the material are described.
Keywords: azides; fragmentations; amines; heterocycles; amides